Nutrition for athletes of complex coordination sports - E. Burlyaeva; D. Nikityuk (National Electronic Information Consortium (NEICON), 2020)
Data on nutrition of athletes of complex coordination sports are analyzed in the review. Some aspects of the metabolism of athletes of these sports are considered in accordance with the specifics of training and competitive loads used in the preparation of an athlete. The influence of some nutrients is discussed in order to get a high result from the training process by improving the physical performance of a person, taking into account the periods of the athlete's work (preparation for training, training, period between training). Based on the analysis of the literature, recommendations on the food and energy value of rations of athletes in complex coordination sports as well as recommendations for the distribution of nutrients, depending on the training process are given.